Missed Opportunity for Routine Immunization and Its Associated Factors in Gozamen District Health Centers, Northwestern Ethiopia - Fetelework Muluneh MPH; Muluken Wubetu MSc; Abebe Abate MSc (SAGE Publishing, 2020)
Background . Vaccine- preventable diseases constitute a major cause of morbidity and mortality in children under-5 years of age in Ethiopia and other developing countries. There are limited studies conducted on this aspect in Ethiopia especially in Gozamen district. Objectives . To assess missed opportunity for routine immunization and its associated factors among children aged <24 months in Gozamen district health centers. Methods . Institutional based cross-sectional study exit interview was conducted on 422 mothers with under 2 years old children. Data was collected using the standard World Health Organization's missed opportunity tool. Vaccines examined in this study were BCG, OPV0, OPV1, PCV1, rota 1, penta valant 1, OPV2, PCV2, rota2, pentavalant 2, OPV3, PCV3, IPV, pentavalant 3, and measles vaccine. The vaccination status of the children was assessed by a structured questionnaire based on vaccination cards or mothers/caregiver verbal responses. Binary and multivariable logistic regression analysis were used to identify factors associated with missed opportunities for routine immunization among children aged <24 months. Result . The prevalence of missed opportunity for this study was 74.9% ; major vaccines with high missed opportunity were OPV0 (67.8), BCG (17.3%), and Measles (14%). Home delivery, lack of vaccination center near the village, unable to attend formal education and younger age (0-12 months) were independently associated with missed opportunity for routine immunization. Conclusion. The prevalence of missed opportunities for routine immunization in Gozamen district health centers was high. Health centers should give routine immunization services regularly.